Proyecto de inversión y desarrollo de una empresa de consultoría para PYMES agroexportadoras en la ciudad de Guayaquil - Silva Paguay, María Alexandra (2019)
The percentage of SMEs that have accounting systems is low which does not allow their information to be up-to-date and accurate, this results in consequences such as penalties for non- compliance with the legal requirements of organizations such as the SRI, Superintendence of companies and other regulatory bodies. Because technology plays an important role in the globalized model of today's economy, SMEs should invest in machinery and software not only to improve their production processes but also their administrative, accounting and financial processes. However, having quality computer systems also represents an obstacle for SMEs because they have to invest thousands of dollars in these acquisitions and entrepreneurs do not see it as an investment but as expenses. In addition to the aforementioned, the lack of knowledge in administrative, accounting and financial matters makes the growth and consolidation in the market of a PYMES company more difficult………